NUMERICAL MODELING OF A TIMOSHENKO FGM BEAM USING THE FINITE ELEMENT METHOD - ZIOU, H.; GUENFOUD, H.; HIMEUR, M.; GUENFOUD, M. (Courrier du Savoir; Vol. 24 (2017): COURRIER DU SAVOIR (Septembre), 2017)
In this paper, a finite element procedure for static analysis of functionally graded material (FGM) beam is presented. The material properties of the beam are assumed to vary continuously along the beam thickness by a power-law distribution. The assumed field displacements equations of the beam are represented by Euler-Bernoulli and first order shear deformation theories. A simply supported beam subjected to uniform load for different length-to-thickness ratio has been chosen. The influences of span-to-depth and the volume fraction index on the mid plane deflections, and stresses distribution along the thickness of the beam are examined. The obtained results are compared with the existing solutions to verify the validity of the developed theories